2006
DOI: 10.1097/01.tp.0000226161.82581.b2
|View full text |Cite
|
Sign up to set email alerts
|

A Significant Role for Histocompatibility in Human Islet Transplantation

Abstract: Patient selection based on sensitization to donor HLA may be one of the factors crucial for the success of islet transplant. Further, in some patients, rejection of islets can be associated with sensitization to mismatched donor histocompatibility antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 24 publications
3
58
0
Order By: Relevance
“…hESC re-injection induced a boost in HLA I IgG antibodies, as has been reported after MSC transplantation in swine (Cho et al, 2008). Even non-cytotoxic alloantibodies detected by flow cross-match, which are negative in conventional complement-dependent lymphocytotoxic cross-match, have been reported to be sufficient to cause immunologic damage of transplanted islets (Mohanakumar et al, 2006). The antibody surge in our study occurred rapidly (within 5 days) and accompanied the strong cellular immune activation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…hESC re-injection induced a boost in HLA I IgG antibodies, as has been reported after MSC transplantation in swine (Cho et al, 2008). Even non-cytotoxic alloantibodies detected by flow cross-match, which are negative in conventional complement-dependent lymphocytotoxic cross-match, have been reported to be sufficient to cause immunologic damage of transplanted islets (Mohanakumar et al, 2006). The antibody surge in our study occurred rapidly (within 5 days) and accompanied the strong cellular immune activation.…”
Section: Discussionsupporting
confidence: 55%
“…The importance of antibody-mediated rejection after cell transplantation is gaining increasing awareness and has already been reported for hematopoietic (Spellman et al, 2010) and mesenchymal stem cell (MSC) transplantation (Beggs et al, 2006;Cho et al, 2008) and for islet transplantation (Mohanakumar et al, 2006). FACS-based DSA quantification using living cells identifies all bound antibodies both against HLA and non-HLA epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from our lab and others have shown that preexisting or de novo production of anti-HLA Abs result in poor islet allograft function (20,26 Figure 6A.…”
Section: Sensitization To Donor Mhc Molecules Increases the Levels Ofmentioning
confidence: 99%
“…Islets from murine pancreata were isolated and transplanted as described in our earlier publicaions (18,19 (20,21 (22). …”
Section: Mouse Islet Isolation Transplant and Immunosuppressionmentioning
confidence: 99%
“…Notably, IAK graft loss occurred without jeopardizing the function of the transplanted kidney (15,19). A positive association between allosensitization and islet graft loss (dysfunction or rejection) has been described in only few sequential ITA recipients (17,20,21), particularly in presensitized recipients (21). (Table 1).…”
mentioning
confidence: 99%